The riddle of the sands: how population dynamics explains causes of high bivalve mortality. Issue 4 (25th June 2013) - Callaway, Ruth; Burdon, Daryl; Deasey, Anna; Mazik, Krysia; Elliott, Michael
Summary: Large‐scale bivalve mortalities in estuarine and coastal habitats are a major environmental and economic concern. They may have obvious causes such as extremely cold winter temperatures, but in the absence of an apparent chain of cause and effect, a rigorous, objective approach is needed to define a probable set of factors responsible for such mortalities. This study interrogates recurrent mortalities of the cockle Cerastoderma edule L. in the Burry Inlet (South Wales, UK), where the causes of the observed die‐offs were obscure. Spatial and temporal patterns in cockle population dynamics were analysed to determine whether mortalities were episodic or continuous, and related to cockle density. Laboratory survival experiments complemented the field studies to indicate the fitness of the cockles. The population dynamics of other species were studied to test for environmental disturbances affecting the entire benthic community. High cockle mortalities occurred throughout the estuary in a specific cohort, namely 1‐year‐old cockles after their first winter. The mortalities did not appear to be episodic, but happened over the spring to early summer months. Cockle densities played a minor role in the decline. The laboratory experiments showed that cockles from the Burry Inlet had higher survival rates than those collected from other areas at early life stages (0‐year class). However, by the time they reached the end of their first year (1‐year class), their survival rates declined significantly. Results suggested a physiological weakness in the cohort after the first winter. Other benthic species did not suffer unusual mortalities. Synthesis and applications . We emphasize that (i) interrogating patterns in population dynamics allows us to limit the number of likely causes of high bivalve mortality and generate more specific hypotheses; (ii) extending studies to other benthic species indicates the likelihood of environmental problems that affect the entire ecosystem; (iii) joined‐up field and laboratory studies suggested that probable causes of cockle mortality were primarily species‐, or even cohort‐specific, biological factors; and (iv) well‐designed monitoring systems will indicate the population dynamics of the target species on spatio‐temporal scales suitable for assessing shifts in the populations, such as unexpected extirpation. Abstract : We emphasize that (i) interrogating patterns in population dynamics allows us to limit the number of likely causes of high bivalve mortality and generate more specific hypotheses; (ii) extending studies to other benthic species indicates the likelihood of environmental problems that affect the entire ecosystem; (iii) joined‐up field and laboratory studies suggested that probable causes of cockle mortality were primarily species‐, or even cohort‐specific, biological factors; and (iv) well‐designed monitoring systems will indicate the population dynamics of the target species on spatio‐temporal scales suitable for assessing shifts in the populations, such as unexpected extirpation.